Transformation in goat farming community at Mukim Batu Talam, Raub, Pahang through KTP program - Kasim, Azhar; Abdul Rahman, Nordin; Saad, Mohd Zamri; Abu Bakar @ Zakaria, Md Zuki; Samsudin, Anjas Asmara @ Ab Hadi; Tajuddin, Zaidi; Amat @ Halimi, Mahani; Jalil, Hairunnisak; Harun, Rostam (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
A two-year Knowledge Transfer Program (KTP) implemented at Mukim Batu Talam, Raub, Pahang in 2011 had propelled the transformation of not only the efficiency in goat farming, but also the income and living standard of goat farmers and family. From an initial of ten families keeping goats as a part-time venture without any government assistance, the multi-faceted activities conducted through the KTP program attracted another twenty families to rear goats. Three of the initial ten families came out as goat farmers with high animal numbers and with highest standard of management of animals. They benefited through additional income from considerable increase in sale of goats. Well-designed hands-on field training on technical aspects of goat rearing increased their confidence level in independent execution of farming tasks such as feeding approach and quick action on animals that need special attention. The visible improvement are goats with better body condition, high twinning rates among does receiving feed supplementation, and early selling age of goats which received better feeding regime. The most glaring change is the less dependence on grass or oil palm fronds as fresh green feed. The naturally grown green biomass around Batu Talam are optimally utilised as new forms of green feeds. These plants included Macaranga species, Acacia species, Glyricidia species, and Leucaena species. This KTP program also focus on housewifes by providing trainings on sewing and cookies making. Housewifes got supplementary income from sales of home-made items. The success of this program indicated that the same approach can be duplicated elsewhere to increase the livelihood of goat farmers and family.